Synergy Between Training and Digital Capabilities: Transforming Competencies to Achieve Competitive Advantage for Retail Apparel SMEs - Shandra Bahasoan; Asniwati Asniwati; Surianto Surianto (Advances in Human Resource Management Research, 2026)
Purpose: This study examines the influence of digital capability and job training on competitive advantage, with employee competence serving as a mediating variable among clothing stores in Bulukumba Regency. Research Method: This study employed a quantitative explanatory design. Data were collected through questionnaires administered to 100 retail employees in Bulukumba, South Sulawesi. Using purposive sampling, the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Results and Discussion: The results indicate that digital capability and job training have a significant effect on employee competence. Employee competence also has a significant effect on competitive advantage, whereas digital capability and job training do not directly affect competitive advantage. In addition, employee competence fully mediates the relationships between digital capability, job training, and competitive advantage. Implications: These findings highlight the importance of human capital development in the retail sector, suggesting that technology adoption and training initiatives enhance competitiveness only when they successfully improve individual employee competence. This study contributes to the small business management literature by emphasizing that, for local retailers, the human aspect of digital transformation and skills development constitutes the critical pathway to achieving a sustainable competitive advantage in a dynamic market.